Iridium-Catalyzed Asymmetric C–H Borylation Enabled by Chiral Bidentate Boryl Ligands - Shi, Yongjia; Gao, Qian; Xu, Senmiao (Synlett, 2019)
Asymmetric synthesis of optically pure organoboron compounds is a topic that has received a number of attentions owing to their particular importance in synthetic chemistry and drug discovery. We herein highlight recent advances in the iridium-catalyzed C–H borylation of diarylmethylamines and cyclopropanes enabled by chiral bidentate boryl ligands.1 Introduction2 Ir-Catalyzed Asymmetric C(sp2)–H Borylation of Diarylmethylamines3 Ir-Catalyzed Enantioselective C(sp3)–H Borylation of Cyclopropanes4 Conclusion
Keywords: chiral boryl ligand; C–H borylation; asymmetric C–H activation; diarylmethylamine; cyclopropane; iridium; asymmetric catalysis